Bridging the Green Gap: Fintech Adoption and Eco-Conscious Luxury Booking Behavior among Generation Z and Millennials — A Systematic Literature Review - Ameresekere Tharindu; Sujeewa Damayanthi Doluwarawaththa Gamage; Jayawardene Ananda; Ranasinghe Asanga (ASEAN Journal on Hospitality and Tourism, 2026)
This systematic literature review examines how fintech-enabled sustainability features influence eco-consciousness on luxury hotel booking intentions among young travelers (Gen Z and Millennials). This review revealed three main themes discussed in the literature: Eco-consciousness of young travelers, which emphasizes how ecological values, awareness shape sustainable travel intentions; Luxury hotel booking intentions, which highlights the influence of perceived value, service quality, Corporate Social Responsibility, and sustainability on booking behavior of young travelers; and Fintech-enabled sustainability features, which shows how digital tools, eco-booking apps, green loyalty programs etc. could improve the relationship between eco-conscious attitudes and actual booking decisions. This review suggests that eco-consciousness shapes young travelers’ sustainable decision-making, and that fintech could strengthen this relationship by making sustainability more rewarding, visible, and accessible. However, as per this literature review, there are still significant gaps: the lack of empirical research investigating how fintech elements affect the degree or trajectory of eco-conscious behavior in luxury hotel booking contexts; a considerable lack of qualitative studies, interdisciplinary perspectives, and cross-cultural grounding.